METHODS OF IMPROVING PRONUNCIATION SKILL IN ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores effective methods for developing pronunciation skills in learners of English as a second language. It offers a range of techniques and tools tailored to different learning styles, enabling learners to choose the most suitable approach for their individual needs.